A Scoping Assessment Of The Literature On The Effects Of Cosmetic Dentistry On Dental Public Health (International Journal of Food and Nutritional Sciences, 2022)
In recent years, cosmetic surgery has witnessed a sharp rise in popularity, and dentistry has followed suit. Concerns regarding the possibility for biological and psychosocial harm from these cosmetic operations were raised by the Department of Health. Additionally, the effects of the expanding use of aesthetic dental operations on dental public health (DPH) have not been investigated. Conduct a scoping review to examine the DPH effects of cosmetic dentistry and pinpoint any open questions for further study. Studies found using the search terms cosmetic AND dentistry underwent a five-stage scoping evaluation. 55 papers (10 cross-sectional studies, 10 literature reviews, and 35 opinion pieces) met the inclusion criteria. Five emerging themes—dento-legal and ethical, marketing, psychological, biology, and workforce—were used to summarize the DPH implications. According to the scoping review, the majority of the literature on cosmetic dentistry is anecdotal—professional discussions and opinions. Despite this, our research showed that the growing demand for aesthetic dentistry had an impact on governance and workforce training. To inform evidence-based policy to protect patients and raise the standard of dental care, more empirical research is required to comprehend the DPH implications of the rising demand and adoption of cosmetic dental operations. A scoping assessment of the literature on the effects of cosmetic dentistry on dental public health.